Epidemiology of ocular surface symptoms and their association with stress levels among the Gazan population in crowded shelters during the 2023 Israel war - Aljarousha, Mohammed; M. Alghamdi, Waleed; Che Azemin, Mohd Zulfaezal; Marliana, Mahmud (Elsevier B.V., 2025)
Purpose To investigate the status of ocular surface symptoms and their relationship to stress levels among the Gazan population during the 2023 Israel-Hamas War. Methods This cross-sectional study involved stratified sampling of participants from the four Gaza districts in Palestine. Individuals aged 18 years or older completed the Arab Ocular Surface Disease Index (Arab-OSDI) questionnaire and the Perceived Stress Scale (PSS-10) to assess stress levels. Results A total of 426 participants (238 males and 188 females) completed the Arabic versions of the OSDI and PSS-10 questionnaires. The mean Arab-OSDI score was 21, with 40.6 % of participants scoring ≥23, the threshold for moderate to severe DED symptoms. Participants with moderate or high perceived stress levels had significantly higher mean Arab-OSDI scores than individuals with low stress levels (p = 0.029). Logistic regression analysis identified age over 50 years, and the high PSS as significant factors associated with Arab-OSDI scores ≥13 (p < 0.05). Conclusion The findings indicate a high prevalence of dry eye symptoms among the Gazan population during the Israel–Hamas war in 2023, with moderate to high perceived stress levels significantly associated with these symptoms